Proč jsou omezená věcná práva omezená? K teoriím o povaze věcných práv a k jejich pojmenování - Matěj Czinege (Acta Universitatis Carolinae. Iuridica)
Limited property rights are a group of rights whose nature is not agreed upon in legal theory and doctrine. On the basis of a doctrinal comparative analysis, three conceivable concepts are identifiable, which are treated inconsistently in the legal literature and, moreover, are combined into incoherent and illogical units that cannot stand up to close scrutiny. The present article identifies the ideal types of these theories, showing by example what their implications are. In addition to these three theories, it simultaneously crystallizes another conception, based on one of these theories, which responds to the shortcomings of the aforementioned theories. This last conception considers limited property rights as independent institutes, which are not derived from ownership but which stand independently alongside it.